Producer Creativity on Documentary Program “Catatan Gen-Z” Edition of “Pemudi Coding dalam Hening” - Fajri Rizki Munif (Jurnal Imiah Teknik Studio, 2022)
Hastu Wijayasri is a brilliant deaf young lady from Yogyakarta, who is internationally-known as the first deaf web developer in Indonesia. Her numerous achievements lead to her being selected as one of Indonesia representative at the prestigious Google I/O web developer conference in San Francisco, USA. With her perseverance, she wants to change people’s view on her as well as the disabled community. As a member of Developer Student Club, Hastu Wijayasri successfully developed an inclusive application named SukaCare. Her success drives the author to share the story with the audience in the television documentary program “Catatan Gen-Z”. The author as the producer chooses “Catatan Gen-Z” as the program name to highlight the achievements of young Indonesian Generation Z. With the applied creativity in this production, the author wishes that the audience would not be bored and keep being entertained. The audience should not pass an educative, informative and entertaining high quality show supported by motion graphics, infographics and 3D effects.